Apakah kontrol diri berkaitan dengan cyberslacking pada siswa sekolah menengah atas? - Aisyah, Nur Ridho; Ramadhani, Hetti Sari; Meiyuntariningsih, Tatik (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2025)
This study examines the relationship between self-control and cyberslacking among high school students in Surabaya. Students' low self-control is a challenge in suppressing deviant internet use behavior during the learning process. The purpose of this study was to determine the extent to which self-control is related to deviant behavior (cyberslacking) in students. This study used a quantitative approach with a correlational design. A total of 345 high school students in Surabaya became respondents using a purposive sampling technique. Data collection was carried out using a questionnaire with a scale that had been tested for validity and reliability. The results of the analysis using the Spearman Rho test showed a significant negative relationship between self-control and cyberslacking, with a coefficient value of -309 and a significance of 0.000 (p